Manual wheelchair training programs: a scoping review of educational approaches and intended learning outcomes - Kimberly Charlton; Carolyn Murray; Natasha Layton; Stacie Attrill (BMC Medical Education)
Abstract Background Training programs grounded in educational theory offer a systematic framework to facilitate learning and outcomes. This scoping review aims to map the educational approaches documented for manual wheelchair training and to record intended learning outcomes and any relationships between learning theories, instructional design and outcomes. Methods Eight databases; Cochrane’s Library, EMBASE, CINAHL, PubMed, Scopus, EmCare, Medline, ProQuest Nursing and Allied Health Database and grey literature were searched in September 2023, with citation chaining for relevant papers. Included papers related to manual wheelchair training programs/protocols describing intended wheelchair training outcomes for adults and/or caregivers. Data extracted included study characteristics, type of intervention, explicit learning theories, instructional design principles and intended learning outcomes. The International Classification of Functioning and Kirkpatrick’s evaluation framework were used to organise intended outcomes. Results Of the forty-four articles included in this review, only fourteen explicitly used a learning theory in the instructional design of training. Training outcomes most commonly related to changes in knowledge/skills of manual wheelchair users (Level 2b of Kirkpatrick’s evaluation (n = 43), with less emphasis on participatory outcomes. Training designs incorporating Social Cognitive Theory (n = 8) were more likely to explore long term training outcomes, compared with other training designs. Conclusion Wheelchair training programs that are designed using learning theory are more likely to produce learning outcomes that are retained and meaningfully applied. Such longer terms outcomes could have systemic cost and efficiency implications, such as reduction in wheelchair falls and readmissions to hospital. Deliberate integration of learning theory into manual wheelchair training design is recommended to support broad outcomes and long-term learning. This design could synergise different learning theories.